2016
DOI: 10.1016/j.snb.2016.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Gated ion transport in a soft nanochannel with biomimetic polyelectrolyte brush layers

Abstract: Functionalized nanofluidics has recently emerged as a powerful platform for applications of energy conversion as well as ionic diodes. Inspired by biological cells, we theoretically investigate for the first time the gate modulation of ion transport and selectivity in the soft nanochannel functionalized with biomimetic, pH-tunable, zwitterionic polyelectrolyte (PE) brush layers. The gate effect on the modulation of Donnan potential, ionic conductance, and ion selectivity in the biomimetic soft nanochannel is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 57 publications
(73 reference statements)
3
39
0
Order By: Relevance
“…This ensures that the contribution of the drag force will be significantly lower since the drag force is calculated by multiplying the drag coefficient with the local velocity and this velocity is smaller at near-wall locations. It might be possible that this overprediction of the drag force in the studies by the other groups (Yeh et al 2012a,b,c;Benson et al 2013;Milne et al 2014;Zeng et al 2014Zeng et al , 2015Poddar et al 2016;Zhou et al 2016;Zimmermann et al 2017;Sadeghi 2018;Sin & Kim 2018;Hsu et al 2019;Huang & Hsu 2019;Lin et al 2019;Reshadi & Saidi 2019;Sadeghi et al 2019;Khatibi et al 2020;Sadeghi et al 2020a,b;Silkina et al 2020;Talebi et al 2021;Wu & Hsu 2021) might have made them miss this enhancement in the electrokinetic transport in brush-grafted nanochannels and that is why they do not provide any explicit comparison between the flow field in a brush-grafted nanochannel with that in a brush-free nanochannel under the condition where the net charge on the wall (for the case of brush-free nanochannel) is distributed on the brushes (for the case of brush-grafted nanochannel). There is another critical issue that has been overlooked by all of these above-mentioned papers, including our own papers.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…This ensures that the contribution of the drag force will be significantly lower since the drag force is calculated by multiplying the drag coefficient with the local velocity and this velocity is smaller at near-wall locations. It might be possible that this overprediction of the drag force in the studies by the other groups (Yeh et al 2012a,b,c;Benson et al 2013;Milne et al 2014;Zeng et al 2014Zeng et al , 2015Poddar et al 2016;Zhou et al 2016;Zimmermann et al 2017;Sadeghi 2018;Sin & Kim 2018;Hsu et al 2019;Huang & Hsu 2019;Lin et al 2019;Reshadi & Saidi 2019;Sadeghi et al 2019;Khatibi et al 2020;Sadeghi et al 2020a,b;Silkina et al 2020;Talebi et al 2021;Wu & Hsu 2021) might have made them miss this enhancement in the electrokinetic transport in brush-grafted nanochannels and that is why they do not provide any explicit comparison between the flow field in a brush-grafted nanochannel with that in a brush-free nanochannel under the condition where the net charge on the wall (for the case of brush-free nanochannel) is distributed on the brushes (for the case of brush-grafted nanochannel). There is another critical issue that has been overlooked by all of these above-mentioned papers, including our own papers.…”
Section: Introductionmentioning
confidence: 96%
“…Without such a comparison, it is not possible to decipher if the results of these papers (Yeh et al 2012a,b,c;Benson et al 2013;Milne et al 2014;Zeng et al 2014Zeng et al , 2015Poddar et al 2016;Zhou et al 2016;Zimmermann et al 2017;Sadeghi 2018;Sin & Kim 2018;Hsu et al 2019;Huang & Hsu 2019;Lin et al 2019;Reshadi & Saidi 2019;Sadeghi et al 2019;Khatibi et al 2020;Sadeghi et al 2020a,b;Silkina et al 2020;Talebi et al 2021;Wu & Hsu 2021) would have shown (for some parameter combination) a flow field that is enhanced in brush-grafted nanochannels, as compared with that in brush-free nanochannels. The second issue is the overprediction of the drag force in these papers (Yeh et al 2012a,b,c;Benson et al 2013;Milne et al 2014;Zeng et al 2014Zeng et al , 2015Poddar et al 2016;Zhou et al 2016;Zimmermann et al 2017;Sadeghi 2018;Sin & Kim 2018;Hsu et al 2019;Huang & Hsu 2019;Lin et al 2019;Reshadi & Saidi 2019;Sadeghi et al 2019;Khatibi et al 2020;Sadeghi et al 2020a,b;Silkina et al 2020;Talebi et al 2021;Wu & Hsu 2021). The drag coefficient dictating the drag force is the gross representative contribution of the presence of the brushes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before long, the leakage current density flowing across the three capacitors in series connection was incorporated into a modified model of the flow field-effect-transistor (flow-FET) by the group of Dutta [ 36 ], to enable a better comprehension of field-effect electroosmosis control in microfluidic networks. Flow-FET has received considerable attention from the microfluidic community over the past two decades [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Most works on this interesting subject have focused on how to improve the pump flow rate from DCEO [ 46 , 47 ], while other kinds of electrokinetic sample manipulations with flow-FET are less of concern for micro-/nano-fluid dynamicists.…”
Section: Introductionmentioning
confidence: 99%
“…Biological pores are widespread in the membrane structure of organisms, which play a vital role in substances transport, energy transmission, signal exchange and other life processes. [1][2][3][4][5][6] It is well-known that the high-efficient screening properties of biological pores stem from the numerous protein synaptophysin with ne structures and the precise functions on the surface of biological pores. [7][8][9][10] Inspired by biological pores, solid-state nanochannels (SSNs) have been developed rapidly and prosperously, which show the superior exibility in terms of geometry, robustness, surface chemical diversity.…”
mentioning
confidence: 99%